2011
DOI: 10.1111/j.1533-2500.2011.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Steroid and Clonidine for Chronic Intractable Post‐thoracotomy Pain: A Pilot Study

Abstract: Our preliminary data suggest possible efficacy of thoracic epidural steroid and clonidine mixture in the treatment of chronic post-thoracotomy pain. No serious adverse effects were noted in this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…VAS scores remained maintained between 0 cm and 3 cm from 2 to 5 weeks following epidural catheter removal. Recently, Ayad and El Masry[23] in a pilot study reported that a combination of epidural steroid and clonidine may provide pain relief in chronic post-thoracotomy pain. The findings of afore mentioned studies have been summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…VAS scores remained maintained between 0 cm and 3 cm from 2 to 5 weeks following epidural catheter removal. Recently, Ayad and El Masry[23] in a pilot study reported that a combination of epidural steroid and clonidine may provide pain relief in chronic post-thoracotomy pain. The findings of afore mentioned studies have been summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Lauretti et al reported the similar efficacy of epidural clonidine and ketamine in chronic cancer pain [26]. Moreover, Ayad and El Masry [8] reported in a pilot study that a combination of epidural steroid and clonidine may provide pain relief in chronic postthoracotomy pain.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-2 agonists had been shown to reduce chronic allodynia in rat animal models [6], most probably through blocking pre- and postsynaptic α -2 receptors [7]. The addition of clonidine ( α -2 agonist) to epidural steroid has been used to treat chronic intractable postthoracotomy pain [8]. …”
Section: Introductionmentioning
confidence: 99%
“…These beneficial effects of clonidine have been demonstrated not only in adult patients but also, in children ( 4 ) and both in patients undergoing general anesthesia ( 1 ), neuraxial block ( 5 - 7 ) and nerve blocks ( 8 ). Even, there are studies that have claimed the role of neuraxial clonidine in decreasing the chronic intractable pain after thoracotomy ( 9 ). But the newly performed studies have claimed that the peripheral and neuraxial effects of clonidine may have some different mechanism of action rather than the previously demonstrated role of clonidine as an alpha 2 adrenoceptor agonist.…”
mentioning
confidence: 99%